Niger : Fifth Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Niger's Fifth Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria. Niger faces daunting development challenges, aggravated by terrorist incursions, climate change, and low uranium export prices. Presidential elections are due in late 2020. Reforms are advancing and economic activity is reasonably strong. Program implementation has been broadly satisfactory. All quantitative targets for end-June 2019 were met. However, a subsequent weakening of revenues, partly due to Nigeria's closure of its borders to trade, as well as topped-up budget support, required mitigating policy measures and the adjustment of end-December 2019 targets. Structural reforms are advancing with delays. Niger can strengthen prospects for a successful transition by securing favorable contractual arrangements with foreign investors; establishing a framework for administering oil resources in line with good practices, notably channeling all revenues directly through the Treasury; and increasing spending on physical and human capital, while being mindful of the inherent volatility in natural resource revenues.